An analysis of the physiological mechanisms for the uptake, accumulation and excretion of gold by Tamarix usneoides E. Mey ex. Bunge - Wilson, Hayden Thorburn (My University, 2020)
Tamarix usneoides E. Mey ex Bunge is an exo-rectretohalophyte riparian tree species that is endemic to arid to semi-arid regions in southern Africa. There has been considerable interest in the genus Tamarixf or its potential for use in erosion control and on environmental rehabilitation sites as it is capable of tolerating a wide range of environmental conditions including fire, varying temperature ranges, saline water, extreme pH and elevated metal salts. The species hyper-accumulates some chloride and sulphate salts and a range of elements have been documented at elevated concentrations in its tissues. This species, as well as T. usneoides X ramosissima hybrids have been planted on gold bearing tailings storage facilities as well as sites contaminated with gold tailings on the Witwatersrand Highveld in order to provide dust control measures and phyto-stabilise the tailings facilities. Prior studies have detected trace quantities of gold in the foliar tissue of T. usneoides and there is interest in the accumulation of gold within the foliar tissue of T. usneoides, as the species is used in phytoremediation of areas contaminated by mining and recovery of gold from contaminated areas could potentially offset the remediation costs. This study aimed to investigate the physiological processes that allow T. usneoides to accumulate gold and other elements within the various tissues of the plant and determine the potential for its use in the recovery of gold from contaminated sites. This was achieved in four separate studies, each of which explored a different aspect of the process of the accumulation of gold and other elements. The in vitro chapter investigated how variables such as gold chemical form, concentration and rhizosphere pH could potentially affect uptake in Tamarix plantlets grown in a liquid media that was dosed with different gold compounds at a range of concentrations and pHs. The in-situ study used plants grown on a gold tailings storage facility in order to localise elemental accumulation within specific tissues as well as to identify how rhizosphere elemental concentrations affect elemental uptake, translocation and accumulation. A microstructural analysis of the salt glands was performed in order to elucidate possible excretion mechanisms for metal salts. An elemental mapping exercise was performed on in vitro material that exhibited the highest gold accumulation values in order to detect which tissues are involved in gold accumulation and relate those findings to the behaviour of other detected elements. The findings showed that T. usneoides is capable of accumulating gold in vitro and that the media pH and gold concentration as well as gold chemical form did affect uptake. The highest concentration of gold in the root tissue was associated with gold chloride trials and the highest concentration in shoot tissue was associated with gold potassium cyanide trials. pH of the growth medium did not affect cutting growth, nor did it affect gold uptake into roots but it did affect gold uptake into shoots, where a lower pH limited gold bioconcentration. In contrast, 5-year old trees grown in-situ on a gold and uranium tailings storage facility showed very low gold concentrations within root, stem or leaf tissue. It is likely that this was due to relatively low gold concentrations in the tailings and low gold bio-availability due to the site-specific geochemical characteristics. The in-situ study demonstrated that T. usneoides regulates elemental concentrations in tissue, with a number of elements remaining bound to the root epidermis and root cortex tissue, while elements that are accumulated are transported to leaf tissue and do not remain bound in the woody biomass. Additionally, an ameliorative effect was observed where tailings samples collected from locations with no trees had a lower pH than areas with trees, suggesting that T. usneoides regulates the conditions of the rhizosphere, which also affects elemental mobility. Studies into the microstructure of the salt glands of the species showed a number of structural adaptations that allowed for the rapid excretion of solutes from the plant. These included adaptations to keep those solutes isolated from the surrounding tissue by transporting them in micro-vesicles and complexing them with polyphenolic compounds. Tissue elemental mapping using wavelength-dispersive spectroscopy illustrated that accumulated elements are partitioned, with chlorine being ubiquitous within tissue while elements such as sodium, calcium and sulphur accumulate within specific cells within the stem mesophyll tissue as well as within the cells containing flocculated polyphenolic compounds. Elemental mapping for gold showed that it followed a similar trend as the accumulation of other lighter elements, albeit at a significantly lower concentration. The findings of this study show that while T. usneoides is capable of accumulating gold when it is supplied in a form that is bioavailable for uptake, site geochemical characteristics will determine the applicability of the species for the recovery of gold from those areas. Thus, the interaction between T. usneoides and the rhizosphere of sites with differing geochemical characteristics warrant additional study. Further studies should also investigate potential ways of increasing gold bioavailability through soil amelioration. The ultrastructural studies and tissue elemental mapping show that T. usneoides can tolerate the elevated solute concentrations within its tissues through a variety of different means, providing insight into the potential mechanisms utilised by other recretohalophyte species to maintain tissue homeostasis
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree Doctor of Philosophy 2020